The Impacts of “General Ordeal” on Changing a Hanafi Fatwa: An applied Study in the Field of Worships - Al Najjar, Mohammad Abd Almannan Saleem (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: The research aims to clarify the impact of general ordeal (ʿumūm al-balwā) according to the Ḥanafī school on legal opinions (fatāwā) and their alteration, demonstrating that the issuing jurist (muftī) is not necessarily bound by the views adopted by earlier jurists of the school. It seeks to elucidate the reasons for considering general ordeal and the contemporary developments associated with it. Methods: The study uses an inductive and analytical approach to elucidate the reasons for general ordeal and its changes, employing deductive inference to derive contemporary applications on issues falling under the realm of general ordeal. Results: The research concludes that general ordeal is among the causes of the alteration of legal opinions in the Ḥanafī school, as it is considered one of the foundational principles for issuing legal opinions in this school. Opinions in such cases consider the mitigation of ordeal and the concept of general ordeal. It also extracts some legal opinions that can be rooted and issued based on the principle of general ordeal. Conclusions: The research demonstrates a clear impact of general ordeal on the alteration of legal opinions in the Ḥanafī school, considering it a fundamental principle for issuing legal opinions. General ordeal has various manifestations stemming from a single reason, which is the difficulty of precaution or its burden. Further studies are recommended on the reasons for the alteration of legal opinions in the Ḥanafī and other schools of thought.